Transparency or Stimulating Meaningfulness and Self-Regulation? A Case Study About a Programmatic Approach to Transparency of Assessment Criteria - Baartman, Liesbeth K. J.; Prins, Frans J. (Frontiers in Education, 2018)
This exploratory case study focused on fostering meaning making of assessment criteria and standards at the module level and the course/programme level (the entire study plan), and the role of self-regulation in this meaning making process. The research questions that guided this study are: (1) How can students’ meaning making of assessment criteria at the module level be fostered, (2) How can students’ meaning making of assessment criteria at the programme level be fostered, and (3) How can self-regulation contribute to students’ meaning making process? We explored the design and implementation of a rather new Master’s programme in The Netherlands: The Master’s Expert Teacher of Vocational Education (METVE). Interviews with three developers, three teachers, and ten students of the METVE were analyzed. For each research question, several themes were derived from the data. Results indicate that meaning making takes place at the module level by using holistic assessment criteria and evaluative experiences, which allow students to make choices within the boundaries set by the assessment criteria. Meaning making at the programme level is experienced as much more difficult by students as well as teachers. The design of the METVE programme fosters meaning making at the programme level, but METVE teachers also express difficulties supporting this. Finally, we found that students perceive self-regulation as something extra for which they don’t have enough time. Self-regulation at the programme level was not explicitly addressed and supported in the METVE, which makes it more difficult for some students to steer their learning process towards the role they are aiming for in professional practice after completing the Master’s programme.